Algebra

posted by .

(2x^3)-(14x^2)+12x=0
x=?

  • Algebra -

    First, factor out the common 2x.
    This leaves you with
    2x[x^2 -6x +6) = 0

    x=0 is one solution. The others are the two roots of
    x^2 -6x +6 = 0,
    which are not integers. You can compute them with the quadratic equation

    x = [6 +/- sqrt(12)]/2 = 3 +/- sqrt3

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Please check Algebra

    Please take a look at my work and let me know if I made any mistakes. You don't have to give me the answers. I'd just like to know if I made any mistakes so that I can correct them. Thanks! 1. 3x – 7 = 8 + 7 +7 3x = 15 3 3 x=5 2. …
  2. math

    The rectangle given has a perimeter of 14 units. Find the value(s) of x by factoring a quadriatic equation. one side= 12/(x+1) other side= 6/(4-x) Remember that the perimeter of a rectangle is: P = 2L + 2W Note: P = perimeter, L = …
  3. math

    how do i do x2+12x+32 x2+12x = 14x+32 subtract 14x from each side 14x=32 divide by 2 7x=16 x=16/7, which is 2 and 2/7 ok maybe you typed that question wrong?
  4. algebra1

    could you walk-through the steps to solving this problem because I am stuck; 3x-5(3x-7)=2(x+9)+45 Let me know if you have a question in any step. 3x-5(3x-7)=2(x+9)+45 3x-15x+35= 2x+18+45 -12x+35 = 2x+63 -35 -35 -12x= 2x +63-35 -12x= …
  5. math

    which equation is equivalent to 5x-2(7x+1)=14x?
  6. algebra

    solve the following equation by clearing fraction want to know if this right -7/3-5/2x=8+2x 6(-7/3)-(5/2)(6)=6(6)+2x(6) 14x-15=48+12x 14x-12x-15=48+14x-14x 2x-15=48 2x-15+15=48+15 2x=-33 2x/2x=-33/2 x=-33/2
  7. algebra

    solve the following equation by clearing fractions show all work want to know if this right -7/3-5/2x=8+2x 6(-2/3)-(5/2x)(6)=6(8)+2x(6) 14x-15=48+12x 14x-12x-15=48+14x-14x 2x-15=48 2x-15+15=48+14x-14x 2x-15=48 2x-15+15=48+15 2x=-33 …
  8. Algebra 1

    1) what is the simplified form of (x-2)(2x+3)?
  9. 9th grade algebra (completing square)

    Can you check the following? A1. (2x + 3)^2 = 25 sqrt(2x + 3)^2 = +-sqrt(25) 2x + 3 = +- 5 2x + 3 = 5, 2x + 3 = -5 2x = 2, 2x = -8 x = 1, x = -4 {-4, 1} A2. x^2 + 14x + 45 = 0 x^2 + 14x + __ = -45 + __ x^2 + 14x + 49 = -45 + 49 (x
  10. Algebra

    Really need some help 1. 14x^2+4+3x-12x^2-3+11x A) 2x^2+7x+1 B) 2x^2+14x+1 C) 2x^2+14x+7 D) 26x^2+7x+7 2. 4x^2+4-5x+x-2x^2+8 A) -2x^2+4x+12 B) -2x^2-4x+12 C) 2x^2+4x+12 D) 2x^2-4x+12

More Similar Questions